Evolution of astacin-like metalloproteases in animals and their function in development - Möhrlen, Frank; Frohme, Marcus (Evolution & development, 2006)
SUMMARY: Astacin-like metalloproteases are ubiquitous in the animal kingdom but their phylogenetic relationships and ancient functions within the Metazoa are unclear. We have cloned and characterized four astacin-like cDNAs from the marine hydroid Hydractinia echinata and performed a database search for related genes in the draft genome sequence of the sea anemone Nematostella vectensis. These sequences and those of higher animals' astacins were subjected to phylogenetic analysis revealing five clusters within the Eumetazoa. The bone morphogenetic protein-1/tolloid-like astacins were represented in all eumetazoan phyla studied. The meprins were only found in vertebrates and cnidarians. Two clusters were taxon-specific, and one cluster represented astacins, which probably evolved after the split of the Cnidaria. Interestingly, grouping of astacins according to the protease catalytic domain alone resulted in clusters of proteins with similar overall domain architecture. The Hydractinia astacins were expressed in distinct cells during metamorphosis and some also during wound healing. Previously characterized cnidarian astacins also act during development. Based on our phylogeny, however, we propose that the developmental function of most of them is not homologous to the developmental function assigned to higher animals' astacins.